2009
DOI: 10.1097/gme.0b013e31819e85c6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravaginal dehydroepiandrosterone (Prasterone) on libido and sexual dysfunction in postmenopausal women

Abstract: By a local action in the vagina, DHEA applied daily at doses at which serum steroids remain well within normal postmenopausal values exerts relatively potent beneficial effects on all four aspects of sexual dysfunction. Such data indicate that combined androgenic/estrogenic stimulation in the three layers of the vagina exerts important beneficial effects on sexual function in women without systemic action on the brain and other extravaginal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(98 citation statements)
references
References 65 publications
2
93
0
3
Order By: Relevance
“…Recent reports support the use of androgens and testosterone in women with vaginal atrophy and research is ongoing into the effectiveness of pilocarpine, a nonselective muscarinic receptor agonist [32][33][34][35][36]. A recently completed trial of intravaginal dehydroepiandrosterone (Prasterone) showed an effect on vaginal atrophy without elevation of estradiol or testosterone above usual postmenopausal levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports support the use of androgens and testosterone in women with vaginal atrophy and research is ongoing into the effectiveness of pilocarpine, a nonselective muscarinic receptor agonist [32][33][34][35][36]. A recently completed trial of intravaginal dehydroepiandrosterone (Prasterone) showed an effect on vaginal atrophy without elevation of estradiol or testosterone above usual postmenopausal levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…41 Despite not having any systemic steroid effects, intravaginal DHEA improved various parameters of sexual function, including domains, such as sexual desire. 42 However, longer-term studies are needed to confirm these data.…”
Section: Androgens and Dehydroepiandrosteronementioning
confidence: 87%
“…W badaniach Labrie'ego i wsp. u kobiet, którym podawano DHEA dopochwowo, odnotowano korzystny wpływ terapii na libido, wyrażający się poprawą w 4 aspektach życia seksualnego: przeżywaniu orgazmu, pożądaniu, pobudzeniu i obecności dyspareunii [11]. Podobnych wyników nie uzyskano podczas doustnego podawania preparatów z DHEA [4].…”
Section: Dehydroepiandrosteron W Miejscowej Terapii Kobiet Z Objawamiunclassified